Spanish Adaptation of the Working Alliance Inventory (WAI). Psychometric properties of the patient and therapist forms (WAI-P and WAI-T) - Andrade-González, Nelson; Fernández-Liria, Alberto (Anales de Psicología / Annals of Psychology, 2015)
The working alliance is one of the most widely studied constructs in psychotherapy process research. The purpose of our study was to adapt the patient and therapist forms of the Working Alliance Inventory (WAI-P and WAI-T) into Spanish. Both measurement instruments were translated into Spanish through a systematic translation process. The psychometric properties of the instruments were evaluated in both a pilot study and a clinical study involving Spanish outpatients with depressive disorders and their therapists. In the clinical study, patients completed the Spanish-language Beck Depression Inventory (BDI) prior to initiating therapy and after the third and tenth psychotherapy sessions. High average scores were obtained with the Spanish-language WAI-P and WAI-T. A large number of individual items correlated satisfactorily with the overall score for the corresponding subscale. Both measures demonstrated excellent reliability (internal consistency) and convergent validity. There were some limitations in the discriminant validity of the measures vs. measures of empathy. Regarding predictive validity, the overall WAI-P and the Task subscale of the WAI-T separately explained a moderate percentage of the variance in patient change in the BDI after the tenth psychotherapy session. These results were satisfactory and consistent with those obtained in studies using the English-language WAI.